Enhancing public service innovation through value co-creation: Capacity building and the ‘innovative imagination’ - Steve Garner (Public Money and Management, 2022)
This article considers how a perspective on value co-creation, known as ‘service-dominant logic’ (S-D logic), contributes to theoretical and empirical understandings of the processes underlying social innovation and co-creation in public services. Specifically, this explores how adopting a service ecosystems perspective to interpret empirical data regarding participation experiences in a UK public service innovation programme, enhances understanding of learning and knowledge exchange processes, experimentation and value co-creation in public service innovation projects.